PENGGUNAAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT DALAM MENINGKATKAN TEAMWORK SKILL MAHASISWA PGSD - Indah Pratiwi (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
This study aims to determine the ability of Teamwork Skill (teamwork), to find out the collaboration of students in learning science materials using the TGT learning model in the experimental class and DI in the control class. The method used in data collection is the Random Cluster research method which is a type of research including quasi-experimental research, the cluster random sampling method selected two sample classes, namely A class as the experimental class taught with the TGT (Team Games Tournament) model with 29 students while the control class taught with direct instruction was chosen class B with the number of students is 28 students. This study involved two classes of samples given different treatments. Student learning outcomes with the TGT cooperative learning model are better than learning outcomes with the DI learning model where the average student learning outcomes in the experimental class are 88.9 while the control class is 73.8. There are differences in learning outcomes between high teamwork skill groups and low teamwork skill groups. The average IPA Learning outcomes between high teamwork skill groups (82.7) were better than the average IPA learning outcomes with teamwork skill groups at a low (69.5).